2014
DOI: 10.1111/jpn.12259
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport and milk secretion during manipulated plasma insulin and glucose concentrations and during LPS‐induced mastitis in dairy cows

Abstract: In dairy cows, glucose is essential as energy source and substrate for milk constituents. The objective of this study was to investigate effects of long-term manipulated glucose and insulin concentrations in combination with a LPS-induced mastitis on mRNA abundance of glucose transporters and factors involved in milk composition. Focusing on direct effects of insulin and glucose without influence of periparturient endocrine adaptations, 18 dairy cows (28 ± 6 weeks of lactation) were randomly assigned to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The elevated basal insulin concentrations in the present study support earlier findings of Tsao et al. () and Lehnen, da Silva, Camacho, Marcadenti, and Lehnen (), who observed higher glycogen resynthesis in skeletal muscles by an increased glucose uptake via the insulin‐sensitive glucose transporter GLUT4 (Gross, van Dorland, Wellnitz, & Bruckmaier, ). Hints for positive impacts of CLA on the immune system were found in rats, chicken, mice (Cook, Miller, Park, & Pariza, ; Ntambi, Choi, Park, Peters, & Pariza, ) and humans (Albers et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The elevated basal insulin concentrations in the present study support earlier findings of Tsao et al. () and Lehnen, da Silva, Camacho, Marcadenti, and Lehnen (), who observed higher glycogen resynthesis in skeletal muscles by an increased glucose uptake via the insulin‐sensitive glucose transporter GLUT4 (Gross, van Dorland, Wellnitz, & Bruckmaier, ). Hints for positive impacts of CLA on the immune system were found in rats, chicken, mice (Cook, Miller, Park, & Pariza, ; Ntambi, Choi, Park, Peters, & Pariza, ) and humans (Albers et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Hötger et al (2013) assumed their findings on the reduced endogenous glucose production in CLAfed cows to reflect the reduced need for glucose, a more efficient use, and a potential glycogen resynthesis in muscle tissue. The elevated basal insulin concentrations in the present study support earlier findings of Tsao et al (2015) and Lehnen, da Silva, Camacho, Marcadenti, and Lehnen (2015), who observed higher glycogen resynthesis in skeletal muscles by an increased glucose uptake via the insulin-sensitive glucose transporter GLUT4 (Gross, van Dorland, Wellnitz, & Bruckmaier, 2015). Hints for positive impacts of CLA on the immune system were found in rats, chicken, mice (Cook, Miller, Park, & Pariza, 1993;Ntambi, Choi, Park, Peters, & Pariza, 2002) and…”
Section: Effects Of Cla Supplementation On Metabolic and Endocrine supporting
confidence: 91%
“…Infusing glucose in early lactation temporarily increased milk yield (Brown and Allen, 2013;Grossen-Rösti et al, 2018), although some authors argued that import capacities via GLUT and sodium-dependent glucose transporters into the mammary gland are limited (Zhao and Keat-ing, 2007b). In mid-to late-lactating cows, we could show that the expression of glucose transporters in the mammary gland seems to not be affected by a shortage of glucose forced by insulin infusion, whereas enzymes and milk components directly depending on glucose as precursor were immediately downregulated (Gross et al, 2015b). Conversely, during a hyperinsulinemic euglycemic condition in which glucose availability was not limited, glucose transporters were even downregulated (Gross et al, 2015b).…”
Section: Endocrine Adaptations Related To Energy and Nutrient Homeostmentioning
confidence: 88%
“…Most of the glucose is taken up into the mammary gland via insulin independent glucose transporter (GLUT) 1 (Zhao and Keating, 2007a,b). At later lactational stages, the importance of insulin-dependent glucose intake by, for example, GLUT4 increases (Mattmiller et al, 2011;Gross et al, 2015b), and the mammary gland is less dominant in draining glucose during an established nutrient homeostasis. The question of whether glucose in early lactation is limiting for milk synthesis was addressed by different approaches.…”
Section: Endocrine Adaptations Related To Energy and Nutrient Homeostmentioning
confidence: 99%
“…During the inflammatory response, research has shown that systemic metabolic changes occur including increased circulating glucose concentrations in lactating dairy cows (Moyes et al, 2014) and nonlactating heifers (Steiger et al, 1999). Hence, glucose may be spared for utilization by phagocytic cells, such as PMNL, rather than the synthesis of milk components in the mammary gland as proposed by Gross et al (2014). During early lactation, glucose availability is low and may partly explain the natural immunosuppression observed at this time.…”
Section: Introductionmentioning
confidence: 91%